1999
DOI: 10.1111/j.1744-618x.1999.tb00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Defining Characteristics of Body Image Disturbance in Japan

Abstract: PURPOSE. To examine the validity of the nursing diagnosis body image disturbance and to specify its major and minor defining characteristics in Japanese culture. METHODS. A qualified sample of 149 RNs with an average of 10 years of clinical experience and knowledge of nursing diagnosis was given a questionnaire consisting of 21 defining characteristics from NANDA, 8 additional items from the literature, and 2 distracting characteristics. FINDINGS. Four major diagnostic content validation (DCV) scores of 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
6

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
0
3
0
6
Order By: Relevance
“…Diversos estudos realizaram a validação de conteúdo de diferentes diagnósticos de enfermagem (LEVIN et al, 1989;WIESEKE et al, 1994;WALL, PHILIPS, HOWARD, 1994;BRUKWITZKI, HOLMGREN, MAIBUSCH et al, 1996;ROSSI et al, 1998;OGASAWARA et al 1999;FU et al 2001;BACHION, ARAÚJO, SANTANA;SANTANA, SAWADA, 2002;BERGAMASCO et al, 2004). No entanto, em relação ao diagnóstico Conhecimento deficiente observou-se que os estudos são escassos e foram desenvolvidos na década de 80 (POKORNY, 1985;POKORNY, 1986;JENNY, 1987;MCKEIGHEN, MEMHMERT, DICKEL, 1989).…”
Section: A Categoria Diagnóstica Conhecimento Deficienteunclassified
See 1 more Smart Citation
“…Diversos estudos realizaram a validação de conteúdo de diferentes diagnósticos de enfermagem (LEVIN et al, 1989;WIESEKE et al, 1994;WALL, PHILIPS, HOWARD, 1994;BRUKWITZKI, HOLMGREN, MAIBUSCH et al, 1996;ROSSI et al, 1998;OGASAWARA et al 1999;FU et al 2001;BACHION, ARAÚJO, SANTANA;SANTANA, SAWADA, 2002;BERGAMASCO et al, 2004). No entanto, em relação ao diagnóstico Conhecimento deficiente observou-se que os estudos são escassos e foram desenvolvidos na década de 80 (POKORNY, 1985;POKORNY, 1986;JENNY, 1987;MCKEIGHEN, MEMHMERT, DICKEL, 1989).…”
Section: A Categoria Diagnóstica Conhecimento Deficienteunclassified
“…Outros estudos realizaram a validação de conteúdo das características definidoras de alguns diagnósticos como: o de Rossi et al (1998), que descreveram o perfil das características definidoras do diagnóstico Déficit de volume de líquidos em pacientes portadores de queimaduras; o de Ogasawara et al (1999), que realizaram a validação do Distúrbio na auto-imagem na cultura japonesa e o de Fu et al (2001), que levantaram evidências para confirmar as características definidoras da Fadiga.…”
Section: Validação Dos Diagnósticosunclassified
“…Many studies have been carried out to refine this diagnosis, by validating its defining characteristics, to determine if they are valid empirical indicators for nursing practice. Among more recent studies, one by Ogasawara et al (1999) in Japan showed that some of the defining characteristics of the diagnosis, as described by NANDA, were difficult for Japanese nurses to understand and, theEfore, were not useful clinical empirical indicators. Also, by comparing the results between the identified defining characteristics and the way they are described by NANDA, they found different clinical behaviors in their sample.…”
Section: Metodosmentioning
confidence: 99%
“…Several studies (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) were found in literature about content validation of different nursing diagnoses. However, it was observed that there are few studies about the "deficient knowledge" diagnosis, most of which were developed in the 1980s (2,6,(18)(19) .…”
Section: Introductionmentioning
confidence: 99%